Geotrigona inusitata, uma nova espécie de Meliponinae do Sudeste do Brasil (Hymenoptera, Apidae) - Moure, Jesús Santiago; Camargo, João M. F. (Acta Biológica Paranaense, 1991)
Geotrigona inusitata, uma nova espécie de Meliponinae do Sudeste do Brasil (Hymenoptera, Apidae)